Elaboration of Legal Anthropology and Anthropolinguistic Studies on the Existence of the Moronene Tribal Community After the Determination of the Hukaea Laea Traditional Area - Alimuddin, Nur Hidayani; Jusafri; Rahmat Alimuddin, Muhammad; Nur Ihsan Halil; Irsan Rahman (Universitas Negeri Semarang, 2025)
Elaboration of legal anthropology and anthropolinguistic studies places the Moronene indigenous people as speakers who live communally with certain standards in maintaining customs and managing natural resources. This research aims to determine the existence of the Moronene indigenous community after the establishment of the Hukaea Laea customary area and to find the concept resulting from the elaboration of legal anthropology and anthropolinguistics studies. This research uses a theoretical (legal anthropology and anthropolinguistic) framework as a guide that serves as a guide for empirical research in the field. The research findings indicate that the implementation of legal anthropology studies to elucidate the existence of the Moronene Indigenous community encompasses the historical recognition of Moronene customary land rights and the legal norms applicable within the community. Meanwhile, the implementation of anthropolinguistics reveals that language is not only a means of communication but also a tool for affirming the existence and sustainability of Indigenous culture. The result of the elaboration of these two fields is the concept of sustainable tourism, that aims to minimize the impact on the environment and socio-cultural aspects while also providing economic benefits to the local community.